Can Subject Speak? - Umar Thamrin; Ridwan Ridwan (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2025)
Why we ask the wrong questions and why we engage in circular reasoning in our debate on subjectivity are the questions I attempt to answer. By applying Greimasian narrative semiotics, I analyze the deep structure of subjectivity and apply the structure to trace the complex layers of subjectivity on which the postcolonial and postmodern critiques are founded. I argue that central to subjectivity is value, and the problem of subjectivity is not to define it but to locate power and desire that constitute the value. They are located in the triangle relationship between subject, object, and sender. The subject desires an object only when the sender creates value for the object. Problematizing and critiquing the position of the subject in the oppressive narrative, or asking who owns the narrative, are the gates to the labyrinth of irrelevant inquiries into subjectivity. This is the underlying reason for the failure of postmodern and postcolonial interventions, for they provide no solution to the ongoing oppression of marginal subjects. Agency and freedom are only myths constituted by the postmodern and postcolonial narratives. The subject is scandalous. It does not exist in its own narrative. The subject never speaks for itself. It is condemned to self-alienation.